Reversible switching of arylazopyrazole within a metal–organic cage - Hanopolskyi, Anton I.; De, Soumen; Białek, Michał J.; Diskin-Posner, Yael; Avram, Liat; Feller, Moran; Klajn, Rafal (Beilstein Journal of Organic Chemistry, 2019)
Arylazopyrazoles represent a new family of molecular photoswitches characterized by a near-quantitative conversion between two states and long thermal half-lives of the metastable state. Here, we investigated the behavior of a model arylazopyrazole in the presence of a self-assembled cage based on Pd–imidazole coordination. Owing to its high water solubility, the cage can solubilize the E isomer of arylazopyrazole, which, by itself, is not soluble in water. NMR spectroscopy and X-ray crystallography have independently demonstrated that each cage can encapsulate two molecules of E-arylazopyrazole. UV-induced switching to the Z isomer was accompanied by the release of one of the two guests from the cage and the formation of a 1:1 cage/Z-arylazopyrazole inclusion complex. DFT calculations suggest that this process involves a dramatic change in the conformation of the cage. Back-isomerization was induced with green light and resulted in the initial 1:2 cage/E-arylazopyrazole complex. This back-isomerization reaction also proceeded in the dark, with a rate significantly higher than in the absence of the cage.
Keywords: arylazopyrazoles; coordination cages; inclusion complexes; molecular switches; photochromism

(untitled) - Narayan, S.; Muldoon, J.; Finn, M. G.; Fokin, V. V.; Kolb, H. C.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2005)

(untitled) - Bain, R. M.; Sathyamoorthi, S.; Zare, R. N. (Angew. Chem., Int. Ed., 2017)

(untitled) - Fallah-Araghi, A.; Meguellati, K.; Baret, J.-C.; El Harrak, A.; Mangeat, T.; Karplus, M.; Ladame, S.; Marques, C. M.; Griffiths, A. D. (Phys. Rev. Lett., 2014)

(untitled) - Kang, J.; Rebek, J., Jr (Nature, 1997)

(untitled) - Hastings, C. J.; Pluth, M. D.; Bergman, R. G.; Raymond, K. N. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, Q.; Tiefenbacher, K. (Nat. Chem., 2015)

(untitled) - Wang, K.; Cai, X.; Yao, W.; Tang, D.; Kataria, R.; Ashbaugh, H. S.; Byers, L. D.; Gibb, B. C. (J. Am. Chem. Soc., 2019)

(untitled) - Li, X.; Liu, D. R. (Angew. Chem., Int. Ed., 2004)

(untitled) - Xu, P.; Kang, L.; Mack, N. H.; Schanze, K. S.; Han, X.; Wang, H.-L. (Sci. Rep., 2013)

(untitled) - Jenkins, S. V.; Chen, S.; Chen, J. (Tetrahedron Lett., 2015)

(untitled) - Chen, J.; Rebek, J. (Org. Lett., 2002)

(untitled) - Yoshizawa, M.; Tamura, M.; Fujita, M. (Science, 2006)

(untitled) - Zhao, H.; Sen, S.; Udayabhaskararao, T.; Sawczyk, M.; Kučanda, K.; Manna, D.; Kundu, P. K.; Lee, J.-W.; Král, P.; Klajn, R. (Nat. Nanotechnol., 2016)

(untitled) - Yoshizawa, M.; Kusukawa, T.; Fujita, M.; Sakamoto, S.; Yamaguchi, K. (J. Am. Chem. Soc., 2001)

(untitled) - Suzuki, K.; Sato, S.; Fujita, M. (Nat. Chem., 2010)

(untitled) - Dri, C.; Peters, M. V.; Schwarz, J.; Hecht, S.; Grill, L. (Nat. Nanotechnol., 2008)

(untitled) - Kusukawa, T.; Fujita, M. (J. Am. Chem. Soc., 1999)

(untitled) - Samanta, D.; Galaktionova, D.; Gemen, J.; Shimon, L. J. W.; Diskin-Posner, Y.; Avram, L.; Král, P.; Klajn, R. (Nat. Commun., 2018)

(untitled) - Qu, D.-H.; Wang, Q.-C.; Zhang, Q.-W.; Ma, X.; Tian, H. (Chem. Rev., 2015)

(untitled) - Petersen, M. Å.; Rasmussen, B.; Andersen, N. N.; Sauer, S. P. A.; Nielsen, M. B.; Beeren, S. R.; Pittelkow, M. (Chem. – Eur. J., 2017)

(untitled) - Wei, J.; Jin, T.-T.; Yin, Y.-F.; Jiang, X.-M.; Zheng, S.-T.; Zhan, T.-G.; Cui, J.; Liu, L.-J.; Kong, L.-C.; Zhang, K.-D. (Org. Chem. Front., 2019)

(untitled) - Huang, H.; Juan, A.; Katsonis, N.; Huskens, J. (Tetrahedron, 2017)

(untitled) - Chu, Z.; Han, Y.; Bian, T.; De, S.; Král, P.; Klajn, R. (J. Am. Chem. Soc., 2019)

(untitled) - Ahrens, J.; Bian, T.; Vexler, T.; Klajn, R. (ChemPhotoChem, 2017)

(untitled) - Zdobinsky, T.; Maiti, P. S.; Klajn, R. (J. Am. Chem. Soc., 2014)

(untitled) - Shichida, Y.; Matsuyama, T. (Philos. Trans. R. Soc., B, 2009)

(untitled) - Simeth, N. A.; Crespi, S.; Fagnoni, M.; König, B. (J. Am. Chem. Soc., 2018)

(untitled) - Calbo, J.; Weston, C. E.; White, A. J. P.; Rzepa, H. S.; Contreras-García, J.; Fuchter, M. J. (J. Am. Chem. Soc., 2017)

(untitled) - Xu, Y.; Gao, C.; Andréasson, J.; Grøtli, M. (Org. Lett., 2018)

(untitled) - Weston, C. E.; Richardson, R. D.; Fuchter, M. J. (Chem. Commun., 2016)

(untitled) - Travieso-Puente, R.; Budzak, S.; Chen, J.; Stacko, P.; Jastrzebski, J. T. B. H.; Jacquemin, D.; Otten, E. (J. Am. Chem. Soc., 2017)

(untitled) - Broichhagen, J.; Frank, J. A.; Trauner, D. (Acc. Chem. Res., 2015)

(untitled) - Velema, W. A.; Szymanski, W.; Feringa, B. L. (J. Am. Chem. Soc., 2014)

(untitled) - Pianowski, Z. L. (Chem. – Eur. J., 2019)

(untitled) - Weston, C. E.; Richardson, R. D.; Haycock, P. R.; White, A. J. P.; Fuchter, M. J. (J. Am. Chem. Soc., 2014)

(untitled) - Stricker, L.; Fritz, E.-C.; Peterlechner, M.; Doltsinis, N. L.; Ravoo, B. J. (J. Am. Chem. Soc., 2016)

(untitled) - Wang, Y.-T.; Liu, X.-Y.; Cui, G.; Fang, W.-H.; Thiel, W. (Angew. Chem., Int. Ed., 2016)

(untitled) - Pandit, R. P.; Kim, S. H.; Lee, Y. R. (Org. Biomol. Chem., 2016)

(untitled) - Stricker, L.; Böckmann, M.; Kirse, T. M.; Doltsinis, N. L.; Ravoo, B. J. (Chem. – Eur. J., 2018)

(untitled) - Niehues, M.; Tegeder, P.; Ravoo, B. J. (Beilstein J. Org. Chem., 2019)

(untitled) - Chu, C.-W.; Stricker, L.; Kirse, T. M.; Hayduk, M.; Ravoo, B. J. (Chem. – Eur. J., 2019)

(untitled) - Lamping, S.; Stricker, L.; Ravoo, B. J. (Polym. Chem., 2019)

(untitled) - Weston, C. E.; Krämer, A.; Colin, F.; Yildiz, Ö.; Baud, M. G. J.; Meyer-Almes, F.-J.; Fuchter, M. J. (ACS Infect. Dis., 2017)

(untitled) - Bian, Q.; Chen, S.; Xing, Y.; Yuan, D.; Lv, L.; Wang, G. (Acta Biomater., 2018)

(untitled) - Wiemann, M.; Niebuhr, R.; Juan, A.; Cavatorta, E.; Ravoo, B. J.; Jonkheijm, P. (Chem. – Eur. J., 2018)

(untitled) - Adam, V.; Prusty, D. K.; Centola, M.; Škugor, M.; Hannam, J. S.; Valero, J.; Klöckner, B.; Famulok, M. (Chem. – Eur. J., 2018)

(untitled) - Zhang, Y.-M.; Zhang, N.-Y.; Xiao, K.; Yu, Q.; Liu, Y. (Angew. Chem., Int. Ed., 2018)

(untitled) - Samanta, D.; Mukherjee, S.; Patil, Y. P.; Mukherjee, P. S. (Chem. – Eur. J., 2012)

(untitled) - Samanta, D.; Gemen, J.; Chu, Z.; Diskin-Posner, Y.; Shimon, L. J. W.; Klajn, R. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Biedermann, F.; Nau, W. M.; Schneider, H.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Biedermann, F.; Uzunova, V. D.; Scherman, O. A.; Nau, W. M.; De Simone, A. (J. Am. Chem. Soc., 2012)

(untitled) - Nishimura, N.; Kosako, S.; Sueishi, Y. (Bull. Chem. Soc. Jpn., 1984)

(untitled) - Bushuyev, O. S.; Singleton, T. A.; Barrett, C. J. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Poprawa-Smoluch, M.; Baggerman, J.; Zhang, H.; Maas, H. P. A.; De Cola, L.; Brouwer, A. M. (J. Phys. Chem. A, 2006)

(untitled) - Ciccone, S.; Halpern, J. (Can. J. Chem., 1959)

(untitled) - Gibson, R. S. L.; Calbo, J.; Fuchter, M. J. (ChemPhotoChem, 2019)